2021
DOI: 10.1002/ccd.29946
|View full text |Cite
|
Sign up to set email alerts
|

Association of peri‐procedural myocardial infarction with mortality after stenting true coronary bifurcation lesions: A pooled individual participant data analysis from four randomized controlled trials

Abstract: Background: Five definitions of peri-procedural myocardial infarction (PMI) following percutaneous coronary intervention (PCI) are used in clinical trials; their clinical relevance in coronary bifurcation stenting remains unclear.Objectives: To understand the correlation between PMI and mortality in bifurcation lesions from the DKCRUSH studies.Methods: PMI was defined using serum creatine kinase-myocardial band (CK-MB) values within 48 h of PCI according to the SYNTAX, Fourth Universal Definition of MI (4th UD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In fact, our result showed a prediction of SB pretreatment for PMI. More recently, Sheiban et al ( 12 ) reported that PMI was positively correlated with TLF at 1-year follow-up after stenting bifurcation lesions. Conclusively, the routine performance of SB pretreatment before the PS procedures was not recommended by the current consortium ( 24 ) and previous clinical trials ( 4 9 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, our result showed a prediction of SB pretreatment for PMI. More recently, Sheiban et al ( 12 ) reported that PMI was positively correlated with TLF at 1-year follow-up after stenting bifurcation lesions. Conclusively, the routine performance of SB pretreatment before the PS procedures was not recommended by the current consortium ( 24 ) and previous clinical trials ( 4 9 ).…”
Section: Discussionmentioning
confidence: 98%
“…Spontaneous MI (after 48 h) was defined as a clinical syndrome consistent with MI with a CK-MB or troponin > 1 × URL and new ST-segment elevation or depression or other findings as above. All MIs were considered TVMI unless there was clear evidence that they were attributable to a non-target vessel ( 4 , 12 ). Clinically driven TLR was defined as angina or ischemia referable to the target lesion requiring repeat PCI or coronary artery bypass graft.…”
Section: Methodsmentioning
confidence: 99%
“…63 Unfortunately, evidence regarding this is scarce; however, it has been shown that PMIs defined by the Society for Cardiovascular Angiography and Interventions (SCAI) criteria, as opposed to the 4th Universal Definition of Myocardial Infarction (UDMI) or the SYNTAX definition, have the best correlation to adverse outcomes after stenting true bifurcations. 64 Furthermore, there are still debates about the most accurate cardiac biomarker to use, although in recent times the cardiology community has seen the extinction of creatine kinase-myocardial band (CK-MB) in favor of high-sensitivity cardiac troponin (hs-cTn). Nevertheless, the correlation among the many available type I hs-cTn assays is unclear and leaves room for potential differences between studies or incorrect endpoint definitions.…”
Section: Myocardial Infarction Periprocedural Myocardial Infarctionmentioning
confidence: 99%